Pediatric dilated cardiomyopathy hearts display a unique gene expression profile - Philip D. Tatman; Kathleen C. Woulfe; Anis Karimpour-Fard; Danielle A. Jeffrey; James Jaggers; Joseph C. Cleveland; Karin Nunley; Matthew R.G. Taylor; Shelley D. Miyamoto; Brian L. Stauffer; Carmen C. Sucharov (JCI Insight, 2017)
Our previous work showed myocellular differences in pediatric and adult dilated cardiomyopathy (DCM). However, a thorough characterization of the molecular pathways involved in pediatric DCM does not exist, limiting the development of age-specific therapies. To characterize this patient population, we investigated the transcriptome profile of pediatric patients. RNA-Seq from 7 DCM and 7 nonfailing (NF) explanted age-matched pediatric left ventricles (LV) was performed. Changes in gene expression were confirmed by real-time PCR (RT-PCR) in 36 DCM and 21 NF pediatric hearts and in 20 DCM and 10 NF adult hearts. The degree of myocyte hypertrophy was investigated in 4 DCM and 7 NF pediatric hearts and in 4 DCM and 9 NF adult hearts. Changes in gene expression in response to pluripotency-inducing factors were investigated in neonatal rat ventricular myocytes (NRVMs). Transcriptome analysis identified a gene expression profile in children compared with adults with DCM. Additionally, myocyte hypertrophy was not observed in pediatric hearts but was present in adult hearts. Furthermore, treatment of NRVMs with pluripotency-inducing factors recapitulated changes in gene expression observed in the pediatric DCM heart. Pediatric DCM is characterized by unique changes in gene expression that suggest maintenance of an undifferentiated state.